Evaluation of the fertilizer and contamination potential of different broiler litter types subjected to various use cycles (2015)
The aim of this study was to evaluate two types of poultry bedding litter (wood shavings and coffee husks) with increasing use cycles, the best time to proceed with composting based on the carbon/nitrogen ratio and the ability to generate ammonia. The results obtained with the present experiment conditions indicated that the litter with wood shavings in the first cycle and the litter with coffee husks in the first and second cycles presented the best behavior in terms of the C/N ratio needed for later use as compost. In regards to the contamination potential, it was found that increasing the number of reutilizations for both the wood-shaving and coffee-husk litters resulted in a greater ammonia emission.